Precision Timing Detectors in Particle Physics: Progress and Challenges in Picosecond Resolution Technologies - J. Va’vra (Current Research Progress in Physical Science Vol. 2, 2024)
The present study seems to cover relevant topics related to picosecond timing detectors and their applications in high-energy physics. The new luminosity upgrades, which are 100-1000 times higher compared to previous generation experiments, will create new demands on detectors. Detector examples discussed: MRPCs, MCP-PMTs, Diamond detectors, SiPMs, Low and high gain Avalanche diodes (LGADs) and Micromegas. We specifically discuss issues such as single pixel vs. multi-pixel tests, small test vs. large physics system results and hidden problems people usually do not want to talk about. Most results in this paper were obtained in small tests, usually with single pixels. The timing resolution will be worse in large complex multi-pixel detector systems with a real background.